2016
DOI: 10.1167/tvst.5.6.15
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma and Driving Risk under Simulated Fog Conditions

Abstract: PurposeWe evaluate driving risk under simulated fog conditions in glaucoma and healthy subjects.MethodsThis cross-sectional study included 41 glaucoma patients and 25 age-matched healthy subjects who underwent driving simulation. Tests consisted of curve negotiation without and with fog preview at 30 m of distance and two controlled speeds (slow and fast). Inverse time-to-line crossing (invTLC) was used as metric to quantify risk; higher invTLC values indicating higher risk, as less time is available to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
0
9
0
18
Order By: Relevance
“…A random subgroup (50% of participants) responding to the survey was invited to undergo a protocol to investigate the association of mobile telephone use while driving with changes in driving performance. A high-fidelity driving simulator (Realtime Technologies Inc) 1 allowed an assessment of driving performance during situations that would be difficult to recreate in the real world without imposing significant risks to the participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A random subgroup (50% of participants) responding to the survey was invited to undergo a protocol to investigate the association of mobile telephone use while driving with changes in driving performance. A high-fidelity driving simulator (Realtime Technologies Inc) 1 allowed an assessment of driving performance during situations that would be difficult to recreate in the real world without imposing significant risks to the participants.…”
Section: Methodsmentioning
confidence: 99%
“…Driving is the main mode of transportation, and the ability to drive is strongly associated with quality of life. 1 , 2 , 3 The National Safety Council's annual injury and fatality report has estimated that the use of mobile telephones while driving is responsible for 26% of motor vehicle crashes. 4 Most of these crashes involve drivers who are distracted by talking on mobile telephones.…”
Section: Introductionmentioning
confidence: 99%
“…5 Prior studies describe the impact of reduced contrast on driving and reading performance in patients with glaucoma. 6,7 However, there has been little to no objective study of mobility in nonideal lighting in this population, and data are needed to better S Time elapsed between first contact and last contact for a single footfall of the dominant leg Swing time S Time elapsed between last contact of the dominant leg footfall and first contact of the next dominant leg footfall Base of support cm Distance between the heel center of the dominant foot and the line of progression created by two subsequent heel strikes of the nondominant leg Double support % cycle time % Percentage of stride time during which both feet are contacting the ground substantiate and understand patient complaints. Even among individuals with normal vision, simulated VF constriction impairs navigation more under scotopic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using repeated scenarios Adler and colleagues showed that drivers with glaucoma are more susceptible to changing their night driving habits on roads in unknown areas, indicating that the simulator may resemble reality (57) . In another recent study, Diniz-Filho and colleagues found that patients with glaucoma had a higher risk of MVCs during foggy conditions than healthy individuals from the control group in a driving simulator, with a higher risk in patients with a mean deviation from visual field lower than -9 dB (58) .…”
Section: Driving Simulatorsmentioning
confidence: 95%